MEMBANGUN ESENSI PENDIDIKAN KARAKTER BERBASIS ISLAM DALAM BUDAYA TASIKMALAYA - Fahri Yanti Fadillah; Aliya Nindy Hapsari; Ichsan Fauzi Rachman (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Tasikmalaya City, located in West Java, serves as a stronghold of Islamic culture and education. Dubbed as the "city of devout students," Islamic values permeate daily life. Communities like Siram Tasik play a vital role in fortifying these values, providing a platform for the youth to learn and grow within Islamic teachings. Islamic education in the city extends beyond religious knowledge, focusing on character formation. Both Islamic and public schools actively implement character education, emphasizing the values of pesantren culture. Despite challenges such as dual perceptions regarding educational documents, these efforts persist. The essence of education in Tasikmalaya City lies in shaping a young generation with strong character, high spirits of struggle, and awareness of Islamic values. The hope is for them to become pillars of integrity, contribute positively to society, and inherit the legacy of goodness from their predecessors.